Depression in patients diagnosed with lupus erythematosus in the lupus erythematosus in the Peruvian Lupus Association (Apelupus), Surco 2014 - Bravo Solsol, Sheyla Solange (2016)
This article aims to determine the level of depression in patients diagnosed with lupus erythematosus in the Peruvian Association of Lupus (Apelupus) and arises as a response to the different psychological symptoms that increase the risk of patients' disease. The research is based on a descriptive and non-experimental design, and a questionnaire was used as an instrument to collect data from a sample of eighty patients diagnosed with this disease. After the analysis and interpretation of the results, it was found that patients with lupus erythematosus present a moderate level of depression compared to the emotions of the environment.